Analysis of spatiotemporal pattern and quantification of gastrointestinal slow waves caused by anticholinergic drugs. (3rd April 2017) - Wong, Kelvin K. L.; Tang, Lauren C. Y.; Zhou, Jerry; Ho, Vincent
ABSTRACT: Anticholinergic drugs are well-known to cause adverse effects, such as constipation, but their effects on baseline contractile activity in the gut driven by slow waves is not well established. In a video-based gastrointestinal motility monitoring (GIMM) system, a mouse's small intestine was placed in Krebs solution and recorded using a high definition camera. Untreated controls were recorded for each specimen, then treated with a therapeutic concentration of the drug, and finally, treated with a supratherapeutic dose of the drug. Next, the video clips showing gastrointestinal motility were processed, giving us the segmentation motions of the intestine, which were then converted via Fast Fourier Transform (FFT) into their respective frequency spectrums. These contraction quantifications were analyzed from the video recordings under standardised conditions to evaluate the effect of drugs. Six experimental trials were included with benztropine and promethazine treatments. Only the supratherapeutic dose of benztropine was shown to significantly decrease the amplitude of contractions; at therapeutic doses of both drugs, neither frequency nor amplitude was significantly affected. We have demonstrated that intestinal slow waves can be analyzed based on the colonic frequency or amplitude at a supratherapeutic dose of the anticholinergic medications. More research is required on the effects of anticholinergic drugs on these slow waves to ascertain the true role of ICC in neurologic control of gastrointestinal motility.